Celebrate Birth!—Ava's Arrival - Reardon, Kim (J Perinat Educ, 2020)
As a Certified Lamaze Childbirth Educator and poet, I wrote this poem to help a new mother come to terms with the fact she was unable to have a vaginal delivery. Her first born was in a transverse lie the entire third trimester. Despite numerous interventions, the baby would not turn and had to be delivered by cesarean surgery. This was the safest possible birth for mother and baby. The couple desperately wanted to hold true to the Lamaze Philosophy and Healthy Birth Practices. They insisted labor begin spontaneously, and so it did. The poem and photographs reveal the parents' fortitude, demonstrating the core premise of their birth plan was not negated. The outcome: healthy mother and healthy baby.